2020
DOI: 10.3389/fmats.2020.00267
|View full text |Cite
|
Sign up to set email alerts
|

Field Strength of Network-Modifying Cation Dictates the Structure of (Na-Mg) Aluminosilicate Glasses

Abstract: Aluminosilicate glasses are materials with a wide range of technological applications. The field strength of network-modifying cations strongly influences the structure of aluminosilicate glasses and their suitability for various applications. In this work, we study the influence of the field strength of network-modifying cations on the structure of [(Na 2 O) 1−x (MgO) x (Al 2 O 3) 0. 25 (SiO 2) 1. 25 ] glasses. Due to the higher cation field strength of magnesium than sodium, magnesium prefers the role of net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 51 publications
3
20
0
Order By: Relevance
“…The trend in relative Q n speciation derived from Raman spectroscopy analysis agrees with the results of Q n speciation obtained by authors through deconvolution of 29 Si MAS NMR spectra for the same series of Na-Mg aluminosilicate glasses [24]. It has been found that replacing Na with Mg in aluminosilicate glasses leads to a reduction in the amount of Q 3 (0Al), Q 3 (1Al), and Q 3 (2Al) species, while the amount of Q 2 (0Al) and Q 2 (1Al) increases.…”
Section: Characterization Of Synthetic Glassessupporting
confidence: 88%
See 1 more Smart Citation
“…The trend in relative Q n speciation derived from Raman spectroscopy analysis agrees with the results of Q n speciation obtained by authors through deconvolution of 29 Si MAS NMR spectra for the same series of Na-Mg aluminosilicate glasses [24]. It has been found that replacing Na with Mg in aluminosilicate glasses leads to a reduction in the amount of Q 3 (0Al), Q 3 (1Al), and Q 3 (2Al) species, while the amount of Q 2 (0Al) and Q 2 (1Al) increases.…”
Section: Characterization Of Synthetic Glassessupporting
confidence: 88%
“…Charge density expressed as cation field strength (CFS) is 0.46 Å –2 for Mg, but 0.18 Å –2 for Na [ 23 ]. The CFS of a network-modifier can have a significant effect on the structure of aluminosilicate glasses [ 24 ]. Hence, Na-Mg aluminosilicate glasses are interesting systems for understanding the effect of CFS on structure.…”
Section: Introductionmentioning
confidence: 99%
“…Binding energy analysis of Table supports this observation: Mg-OAl 2 has the strongest binding energy among Mg-BO and has the binding energy slightly lower than [3] Mg-NBO and greater than [4] Mg-NBO. Experimental observations also pointed out the higher binding energy of network-modifying cations in aluminosilicate glass to Al-connected oxygen and the binding energy of Mg–O increases especially if the Mg 2+ cations behave as a charge compensator. , …”
Section: Resultsmentioning
confidence: 95%
“…Glass cations can be categorized as network formers, network modifiers, and intermediates based on their field strength values: cations with relatively higher field strength ( F > 1.3) prefers network formers, cations with a smaller field strength ( F < 0.4) becomes network modifiers, and intermediates (0.4 < F < 1.3) can behave as network formers or modifiers. The trend from a field strength theory agrees well with Zachariasen’s glass cation categorization for network formers, network modifiers, and intermediates in general. Inside the glass, the oxygen connecting two network formers becomes the BO (bridging oxygen), forming the relatively shorter and stronger covalent bond with cations of the glass backbone network. In contrast, the NBO (non-bridging oxygen) connects the network modifier and network former, providing a relatively longer and weaker connection to the glass structure and cannot participate in the tetrahedral network. , Such weak interactions between NBO and network modifiers govern thermodynamic and mechanical properties of the overall glass structure. Especially, the recent study suggests that the modifier cations with higher field strength, such as Mg 2+ , Ca 2+ , and Mn 2+ , can influence the local coordination environment, the amount of NBOs, and the local structure of the glass. It has been observed that as the cation field strength of network modifier ions increases, they exert more influence on the structure and mechanical properties of multi-oxide glasses such as Young’s modulus and bulk modulus. …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the decreases of field strength as shown in table 1 supports this result. A BO atom carries less negative charge than that of an NBO atom [40].…”
Section: Density and Thermal Propertiesmentioning
confidence: 99%